2012
DOI: 10.1371/journal.pone.0038786
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glutamatergic Compounds in Pregenual Anterior Cingulate in Pediatric Autism Spectrum Disorder Demonstrated by 1H MRS and 1H MRSI

Abstract: Recent research in autism spectrum disorder (ASD) has aroused interest in anterior cingulate cortex and in the neurometabolite glutamate. We report two studies of pregenual anterior cingulate cortex (pACC) in pediatric ASD. First, we acquired in vivo single-voxel proton magnetic resonance spectroscopy (1H MRS) in 8 children with ASD and 10 typically developing controls who were well matched for age, but with fewer males and higher IQ. In the ASD group in midline pACC, we found mean 17.7% elevation of glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 114 publications
10
78
2
1
Order By: Relevance
“…Cochran et al [33] found higher glutamine (Gln) levels and lower GABA/Cre levels in ASD, supporting the idea of an excitatory (Glu)/inhibitory (GABA) imbalance hypothesis. Anterior cingulate NAA, t-Cho, Cre, and mI signals were also found to be altered in some earlier studies [9, 10, 31, 3437]. In the left dorsolateral prefrontal cortex (DLPFC), low NAA/Cre levels were found in the study by Fujii and colleagues [36], but no significant differences were found in two other studies [34, 38].…”
Section: Introductionmentioning
confidence: 76%
“…Cochran et al [33] found higher glutamine (Gln) levels and lower GABA/Cre levels in ASD, supporting the idea of an excitatory (Glu)/inhibitory (GABA) imbalance hypothesis. Anterior cingulate NAA, t-Cho, Cre, and mI signals were also found to be altered in some earlier studies [9, 10, 31, 3437]. In the left dorsolateral prefrontal cortex (DLPFC), low NAA/Cre levels were found in the study by Fujii and colleagues [36], but no significant differences were found in two other studies [34, 38].…”
Section: Introductionmentioning
confidence: 76%
“…This further highlights how early developmental abnormalities may have repercussions later on. It is also important to note that E/I imbalance studies have mainly been carried out in animal models, hence a detailed evaluation of when, where and how an E/I shift contributes to the ASD phenotypes in humans is warranted 161163 .…”
Section: Neurobiological Models and Mechanisms Of Asdmentioning
confidence: 99%
“…Glx levels were not significantly correlated with IQ or autism symptom measures. Several other groups have reported significantly increased glutamate concentration since then in regions including the anterior cingulate gyrus (Joshi:2012ir; Bejjani et al 2012) and auditory cortex (Brown et al 2013). Others have reported reduced Glx in autism or no group differences in similar regions of interest (DeVito et al 2007; Bernardi et al 2011; Horder et al 2013).…”
Section: In-vivo Evidence Of Increased Glutamate In Autismmentioning
confidence: 99%